Hydrogen Sulfide, Adipose Tissue and Diabetes Mellitus - Zhu L (Dove Medical Press, 2020)
Lin Zhu,1 Bo Yang,2 Dongxia Ma,3 Lan Wang,4 Wu Duan5 1Department of Pediatrics, Tongji Hospital, Tongji Medicine College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 2Institute of Organ Transplantation, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 3Department of Allergy, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 4Reproductive Medicine Center, Tongji Hospital, Tongji Medicine College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 5Division of Endocrinology, Department of Internal Medicine, Qilu Hospital of Shandong University, Jinan 250012, People’s Republic of ChinaCorrespondence: Wu DuanDivision of Endocrinology, Department of Internal Medicine, Qilu Hospital of Shandong University, Jinan 250012, People’s Republic of ChinaTel/ Fax +86-531-8692-7544Email duan5wu@qq.comAbstract: Hydrogen sulfide (H2S) is now increasingly considered to be the third gasotransmitter alongside other gaseous signaling molecules, nitric oxide (NO) and carbon monoxide (CO). H2S is produced by a variety of endogenous enzymatic and non-enzymatic pathways and acts as a modulator of the physiological and pathological events of the body. Adipocytes express the cystathionine γ lyase (CSE)/H2S system, which modulates a variety of biological activities in adipose tissue (AT), including inflammation, apoptosis, insulin resistance, adipokine secretion and adipocyte differentiation. Abnormalities in the physiological functions of AT play an important role in the process of diabetes mellitus. Therefore, this review provides an overview of the general aspects of H2S biochemistry, the effect of H2S on AT function and diabetes mellitus and its molecular signalling mechanisms as well as the potential application of H2S in pharmacotherapy.Keywords: hydrogen sulfide, adipose tissue, diabetes mellitus, drug therapy